Seksualitas dan Implikasinya dalam Kehidupan Rumah Tangga Perspektif Sosiologi Hukum Islam - Fadli Sukriani Melu; Rizal Darwis (Al-Mizan (e-Journal), 2021)
Fulfillment of conjugal right, especially sexuality in married couples is important and must be carried out. This paper discusses the sociological analysis of Islamic law related to sexuality and its implications in marriage. This research is a literature review with a sociological approach to Islamic law. The data collected were analyzed descriptively and qualitatively. The results showed that the harmonious relationship between husband and wife can affect the health of the couple's sexual behavior; and vice versa, the health of husband-and-wife sexual behavior can affect the harmony of the couple's relationship. Sexual fulfillment as a form of husband and wife's inner livelihood rights can create a sense of happiness so that the purpose of marriage is realized, namely peaceful (sakinah), love (mawaddah), and affection (wa rahmah).